Magnetized mixed convection second‐grade fluid flow adjacent to a lubricated vertical surface. Issue 6 (25th June 2020) - Ahmad, Manzoor; Shehzad, S. A.; Taj, Muhammad; Ramesh, G. K.
Abstract: The aspects of magnetized mixed convection in second‐grade fluid flow near stagnant point induced by vertical wall are reported. The fluid is impinging orthogonally on the power law lubricant surface. The convective surface temperature and concentration distribution have been assumed. Both the lubricant and the base fluid are governed by the partial differential mathematical expressions. The velocity of the second‐grade fluid and the lubricant are supposed to be continuous at interface. To get the solution of defined nonlinear problem, an implicit numerical technique namely Keller‐Box scheme is applied. The influential constraints are visualized by plotting graphs on velocity, concentration, and thermal profiles. The results of skin‐friction factors, and mass and heat transport rates for both opposing and assisting flows are tabulated and evaluated. The obtained results are validated through available data for limiting conditions.